Exploring a Family-Based Oral Health Promotion Model for Dental Caries Prevention among School-Aged Children: A Qualitative Study - Febi Magfirah; Faradillah Usman (Jurnal Ilmu Kesehatan Nusantara, 2025)
Background: Dental caries remains common among school-aged children and can cause pain, infection, eating difficulties, school absence, and reduced quality of life. Because children’s daily oral health practices develop mainly within families, prevention requires active caregiver participation. Research Objective: This study aimed to explore experiences, perceptions, barriers, facilitators, and expectations regarding a family-based oral health promotion model for dental caries prevention. Methods: This qualitative descriptive study involved 24 participants: eight children, eight parents, four teachers, two community health workers, and two dental professionals. Participants were recruited purposively. Data were collected through semi-structured interviews and focus-group discussions and analysed thematically. Trustworthiness was supported through triangulation, member checking, peer discussion, and an audit trail. Results: Five themes emerged: caries was considered a minor problem; children’s oral hygiene was inconsistent; family behaviour shaped children’s habits; families experienced practical, social, and economic barriers; and integrated family–school–healthcare collaboration was required. Participants proposed education, parental modelling, supervised toothbrushing, reduced sugar exposure, school reinforcement, and regular dental screening. Conclusion: Dental caries prevention requires coordinated support from families, schools, and healthcare providers. The proposed model may strengthen sustainable preventive behaviour but requires feasibility testing and outcome evaluation in diverse communities.